2019
DOI: 10.1002/ptr.6446
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant‐like effects of 20(S)‐protopanaxadiol in a mouse model of chronic social defeat stress and the related mechanisms

Abstract: 20(S)-Protopanaxadiol (PPD) is a basic aglycone of the dammarane triterpenoid saponins and exerts antidepressant-like effects on behaviour in the forced swimming test (FST) and tail suspension test (TST) and in rat olfactory bulbectomy depression models.However, the antidepressant effects of PPD have not been studied thoroughly. The objective of the present study was first to investigate the effect of PPD on depression behaviours induced by chronic social defeat stress (CSDS) in mice. The results showed that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 55 publications
3
14
0
Order By: Relevance
“…The FST test results showed that SY improved the despair behavior in that SY significantly shortened the enhanced immobility durations in mice induced by CSDS. Collectively, we found that 4‐week CSDS induces a variety of depressive behavioral changes in animals, including anhedonia, social avoidance and despair behavior, consistent with previous studies (Jiang, Lv, Wang, Wang, et al, 2019). As expected, consecutive treatment with SY completely reversed these behavioral deficits.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The FST test results showed that SY improved the despair behavior in that SY significantly shortened the enhanced immobility durations in mice induced by CSDS. Collectively, we found that 4‐week CSDS induces a variety of depressive behavioral changes in animals, including anhedonia, social avoidance and despair behavior, consistent with previous studies (Jiang, Lv, Wang, Wang, et al, 2019). As expected, consecutive treatment with SY completely reversed these behavioral deficits.…”
Section: Discussionsupporting
confidence: 91%
“…The SPT was performed for a duration of three consecutive days, including a two‐day sugar water adaptation phase and a one‐day test phase (Jiang et al, 2019). On the first two days (at 9:00 a.m.), each mouse was concurrently presented with two bottles containing 100 ml of either 1% sucrose solution or tap water, the animals had access to food/liquids ad libitum, and the location of the water bottles was altered every 12 hrs to minimize potential location bias.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The social interaction test (SIT) comprised two 150‐s trials (Lin et al, 2018). The apparatus is a social interaction open field arena (40 × 40 × 40 cm), made of a white plastic material, with an empty wire‐mesh plexiglas enclosure (7 × 10 × 40 cm) located in the social interaction (SI) zone (13.5 × 24.0 cm) (Jiang et al, 2019). In the first phase, each mouse was placed along the center of the opposite wall and allowed to explore freely for 150 s. In the second phase, the mouse was re‐introduced into the box located in the middle of one of the walls of the open field with an unfamiliar aggressor CD‐1 mouse (“target” conditions) and allowed to explore again for 150 s. The time that the experimental mouse spent in the interaction zone under target conditions, and when a target was absent, was recorded by a camera.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as previously reported (Jiang et al, 2019; Lu et al, 2018). The dissected hippocampus and PFC tissues were homogenized in RIPA (radioimmunoprecipitation assay buffer) with a protease and phosphatase inhibitor cocktail (Sigma Aldrich).…”
Section: Methodsmentioning
confidence: 99%